Effectiveness of Mobile Health Applications in Improving Medication Adherence among Hypertension Patients - Ahmad Rizki; Mei Ling Chen (Media of Health Research, 2025)
Hypertension remains a major global health concern due to its high prevalence and association with cardiovascular complications. Poor medication adherence is one of the leading factors contributing to uncontrolled blood pressure, resulting in adverse health outcomes. Recent advances in digital health, particularly mobile health (mHealth) applications, have been widely used to support self-management of chronic diseases. This study aimed to evaluate the effectiveness of mHealth applications in improving medication adherence among hypertensive patients. A quasi-experimental study was conducted with 120 participants randomly assigned into intervention and control groups. The intervention group used an mHealth application designed to provide medication reminders, educational content, and self-monitoring tools for 12 weeks, while the control group received standard care. Adherence levels were measured using the Morisky Medication Adherence Scale (MMAS-8), and blood pressure control was also assessed. Results indicated a significant improvement in adherence scores in the intervention group compared to the control group (p < 0.01). Additionally, systolic and diastolic blood pressure levels were better controlled among patients using the application. These findings suggest that mHealth applications can effectively enhance medication-taking behavior and contribute to better hypertension management. Further studies with larger samples and longer follow-up are recommended to confirm long-term sustainability and cost-effectiveness.